Sedimentation on the continental margin off the Orange River and the Namib Desert - Rogers, John (Department of Geological Sciences, 2023)
This study is the first detailed reconnaissance survey of the bathymetry, bedrock geology and the superficial sediments of the continental margin off the Orange River and the Namib Desert. The study area is bounded by latitudes 25° and 3o0 s. The Orange shelf is up to 100 km wide and 200 m deep, and the Walvis shelf off Lllderitz is up to 80 km wide and 400 m deep, the inner shelf is underlain by. Precambrian bedrock and is usually less than lOi km wide and shallower than 100 m. Tripp Seamount penetrate the upper slope in a depth of 1000 m and rises to within 150 m of sea level, the level of the Orange Banks on the outer orange shelf. South of the Orange River unfossiliferous ferruginous sandstones and mudstones crop out as seaward-dipping scarps on the middle shelf. North of the Orange River, similar scarps are composed of quartzose lime wackestones, identical to a Palaeogene suite on the Agulhas Bank. The shallow outer orange shelf is underlain in places by Upper Middle Miocene nummulitic _limestones, which are overlain by glauconitic conglomeratic phosphorites. Quartz-free algal limestones are found both on the Orange Banks and on the tip of Tripp Seamount. Authigenic pyrite and gypsum were found in two samples of semi-consolidated Neogene clay on the slope off Lüderitz. Pyrite is formed by combining teErigen-. ous adsorbed iron with sulphur released by anaerobic reduction of sea-water sulphate. The dissolution of planktonic foraminiferal tests provides calcium ions which combine with sulphate to form gypsum, once the calcium/sulphate solubility product is exceeded. On the Walvis shelf off LUderitz residual glauconite was reworked from older Neogene sediments, particularly on Lllderitz Bank. North of latitude 26°S residual phosphorite pellets were probably formed in Neogene diatomaceous oozes and then concentrated during a Late-Tertiary regression. Erosion of semi-consolidated .Neogene clays and ?Palaeogene quartzose' limestones. on ·the middle and outer Walvis shelf led to deposition of very fine residual quartz sand south of LUderitz. Coarse quartz ~and was reworked from littoral sandstones on the middle shelf south of the Orange River. The effect on sedimentation in the hinterland of poleward shifts of climatic belts during Quaternary interglacials and the reverse movement during glacials is assessed. Recent terrigenous sediments are derived by erosion of poorly consolidated Karoo sediments in the catchment of the Upper Orange. Erratic but powerful floods transport the sediments to the coast in suspension each summer. At the mouth in tense wave action dominates the submarine delta of the Orange River and fractionates the sediment load. Sand is transported equatorwards by littoral drift and is blown off beaches towards the Namib Sand Sea during violent Trade-Wind gales each sunnner. In contrast, silt and clay are transported polewards by a countercurrent, particularly during westerly winter storms. Recent biogenic sedimentation is controlled by upwelling in the B~nguela Current System, which is most intense off the wind dominated Sperrgebiet, south of LUderitz. Weaker upwelling off the Orange River allows oceanic planktonic foraminifera to penetrate to the middle shelf, whereas on the Walvis shelf in the study area they only reach the outer shelf. Towards latitude 25°s the Benguela Current System decays and interacts with poleward-flowing warm oxygen-poor water. Periodic mass mortalities of oxygen-starved phytoplankton lead to some of the most organic-rich sediments in the world.